Pengaruh Kualitas Layanan Dan Citra Merek Terhadap Keputusan Pembelian The Body Shop Mall Olympic Garden Malang - An Nida’ Sayyid Al Mahdi; Rena Feri Wijayanti (Jurnal Publikasi Ilmu Manajemen, 2025)
This research was a quantitative study with two independent variables, namely service quality (X1) and brand image (X2) as well as variables dependent by purchasing decisions (Y). The data collection method was by observation and questionnaire, and using incidental sampling techniques on 100 respondents. Data was then analyzed using regression analysis, regression coefficients and hypothesis tests. The results of multiple linear regression analysis showed Y' = 2.537 + 0.281X1 + 0.664X2 with Adjusted R Square obtained of 0.577. With a multiple coefficient of determination value (R2) of 0.585 which meant that the magnitude of the contribution of the influence of service quality variables (X1) and brand image (X2) on the purchasing decision (Y) the Body Shop Mall Olympic Garden Malang was 57.7% while the remaining 42.3% was influenced by variables that were not studied in this study